2018
DOI: 10.1055/s-0038-1642033
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Vitamin D Preserves Placental Vascular and Fetal Growth in Experimental Chorioamnionitis Due to Intra-amniotic Endotoxin Exposure

Abstract: IA ETX decreases placental growth and vessel density and decreases placental VDR and CYP27B1 protein expression, and that antenatal 1,25-(OH)D restores placental weight and vessel density, as well as birth weight. We speculate that 1,25-(OH)D treatment preserves placental function in experimental CA and that these effects may be mediated by increased vascular growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 62 publications
2
12
0
Order By: Relevance
“…In a further study by Cookson et al, 24 it was found that prenatal supplementation with 1,25(OH) 2 D 3 could restore birth weight, blood vessel density, and placental weight. They also reported that vitamin D increased placental blood vessel growth by stimulating the growth of endothelial cells and increasing the expression of vascular endothelial growth factor 24 . Mandell et al 25 established a BPD rat model by prenatal intraamniotic injection of ​endotoxin.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In a further study by Cookson et al, 24 it was found that prenatal supplementation with 1,25(OH) 2 D 3 could restore birth weight, blood vessel density, and placental weight. They also reported that vitamin D increased placental blood vessel growth by stimulating the growth of endothelial cells and increasing the expression of vascular endothelial growth factor 24 . Mandell et al 25 established a BPD rat model by prenatal intraamniotic injection of ​endotoxin.…”
Section: Discussionmentioning
confidence: 91%
“…Studies have reported that the histological evidence of insufficient placental vascular perfusion is closely related to the high incidence of fetal growth restriction and BPD, but the mechanism for increased susceptibility is not clear 22,23 . In a further study by Cookson et al, 24 it was found that prenatal supplementation with 1,25(OH) 2 D 3 could restore birth weight, blood vessel density, and placental weight. They also reported that vitamin D increased placental blood vessel growth by stimulating the growth of endothelial cells and increasing the expression of vascular endothelial growth factor 24 .…”
Section: Discussionmentioning
confidence: 97%
“…Formalin-fixed, paraffin-embedded placental tissue sections (5 mm) were used for hemotoxylin and eosin (H&E) and CD34 (vascular endothelial marker) staining and processed for histological staining and immunohistochemistry to assess placental vascularity. The CD34-stained slides were quantified for vascularity using the Matlab Image Processing Toolbox (MathWorks, Natick, MA, USA) as previously described in Cookson et al (25). Fields of view were captured across the placenta at 320 magnification.…”
Section: Assessment Of Placental Vascularitymentioning
confidence: 99%
“…More recently, direct demonstration of the importance of Vitamin D in pregnancy and BPD has been obtained from experiments in which antenatal Vitamin D supplementation was associated with improved placental vascularization and fetal growth. 78 Postnatal Vitamin D supplementation was associated with an improvement in alveolarization in rats that were exposed to intra-amniotic LPS, 79 and Vitamin D induced downregulation of TLR4 and therefore decreased downstream cytokines such as IL1ß in neonatal rats exposed to hyperoxia. 80 The effects of Vitamin D on the activation of eNOS likely contribute to the beneficial observations with Vitamin D both on the placenta and postnatal vascular and alveolar growth.…”
Section: Vitamin Dmentioning
confidence: 95%